THE RELATIONSHIP BETWEEN TEACHER SERVICE AND COUNSELING WITH CLASS VIII STUDENT SATISFACTION 2019/2020 ACADEMIC YEAR IN MTS NEGERI 2 BANYUWANGI - Harwanti Noviandari; Robbaniyah Inayatur; Ahmad Sulthoni (International Jurnal of Education Schoolars, 2020)
Therefore, researchers are interested in conducting this research with the aim of knowing the relationship of guidance and counseling teacher services with the satisfaction of class VIII students in the 2019/2020 school year. This research was conducted at MTs Negeri 2 Banyuwangi. This research is a quantitative type with a descriptive approach, using a questionnaire method as a data collection tool. The research population was students of class VIII MTs Negeri 2 Banyuwangi with a total of 224 students, from the number of papulations then the sample was taken using themethod proportional random sampling so that the sample in this study amounted to 56 respondents. Because the purpose of this study is to describe and explain the relationship of guidance and counseling teacher services with satisfaction. This research was conducted in steps: determining the location of the study, determining the research method, determining the types and sources of data, and analyzing the data. Data processing in this study using the help of SPSS For Windows 23.00. The results of the research after calculating with SPSS For Windows 23.00, namely there is a relationship between guidance and counseling teacher services with satisfaction, this is in accordance with the significance results of 0.000 <0.05, so that the alternative hypothesis which reads "There is a relationship between guidance and counseling teacher service with student satisfaction. class VIII of the 2019/2020 school year ". The degree of relationship in this study was 46.2%, so the remaining value of 53.8% was influenced by other factors not examined in this study.